Amarante nos Caminhos de Santiago - Daniel Ribeiro (Ad Limina, 2025)
The geographic position of Amarante, in North of Portugal, it is in an enclave between the Minho’s Coast and the mountains of Trás-os-Montes, it will would be a determinant condition to pass a lot of travelers, among them merchants and pilgrims. This constant affluence of people and assets boosted the settlement of Amarante; the reconstruction of an ancient bridge over the River Tâmega; and the fixation of a Dominican hermit, who has deceased in grace, Saint Gonzalo of Amarante. By being a place with a lot of movement, in Amarante settled down, two hostels that associated with others cultural elements, gave to Amarante cultural characteristics very specifics, such has hospitality.